Soil Creep Effect on Time-Dependent Deformation of Deep Braced Excavation - Panpan Guo; Gang Lei; Lina Luo; Xiaonan Gong; Yixian Wang; Baojian Li; Xunjian Hu; Haibo Hu (Advances in Materials Science and Engineering)
This paper describes recent advances in the effect of soil creep on the time-dependent deformation of deep braced excavation. The effect of soil creep is generally investigated using the observational method and the plain-strain numerical simulation method. The observational method is more applicable for deep braced excavations in soft clays constructed using the top-down method. The plain-strain numerical simulation method can be conveniently used for parametric analysis, but it is unable to capture the spatial characteristics of soil creep effect on lateral wall deflections and ground movements. The additional lateral wall deflections and ground movements that are generated due to the soil creep effect can account for as large as 30% of the total displacements, which highlights the importance of considering the effect of soil creep in deep braced excavations through soft clays. The magnitude of the displacements due to soil creep depends on various factors, such as excavation depth, elapsed period, unsupported length, and strut stiffness. Parametric analyses have indicated several effective measures that can be taken in practice to mitigate the detrimental effect of soil creep on the deformation of deep braced excavation. Based on the literature review, potential directions of the related future research work are discussed. This paper should be beneficial for both researchers and engineers focusing on mitigating the adverse effect of soil creep on the stability of deep braced excavations.